पाणिनि व्याकरणमा द्विरुक्तिविज्ञानको रूपरेखा - Gyawali, Hare Krishna (Haimaprabha, 2025)
The present discussion is related to the system of double entendre in Paninian grammar. Double entendre means repetition and in a broad sense repetition is the process of repeating a linguistic form or meaning. This sometimes results in the formation of new words and sometimes in the style of rhetoric. In Paninian grammar, not only are there many formulas for this special system, but there is also a scientific study of the subject of double entendre in Sanskrit language. Although there has been extensive research and study on other aspects of Paninian grammar, there is not much study on this double entendre and the science of double entendre. In this article, the objective is to explore various aspects of the double entendre system in Paninian Ashtadhyayi, taking this vacant subject as a problem. Since the qualitative approach is followed, sample materials have been sought from library studies for this. In this process, Paninian Ashtadhyayi has been used as the primary source and facts have been collected, while necessary information has also been collected from secondary sources. After thorough verification of the collected material, an interpretive and descriptive method has been adopted for the presentation and discussion of the factual material. Since the discussion of double entendre in Panini's grammar in the form of formation, etymology, style of speech and the process of double pronunciation are obtained through discussion and analysis. It has been concluded that Panini's study of double entendre was carried out at three levels: theoretical, experimental and phonetic.